EARNINGS AND CAPITAL MANAGEMENT THROUGH LOAN LOSS PROVISIONS IN INDONESIAN BANKS AFTER IFRS 9 IMPLEMENTATION - Haq, Qadri Fidienil (Jurnal Akuntansi dan Keuangan Indonesia, 2023)
This study aims to examine whether Indonesian banks perform earnings and capital management through loan loss provisions and whether IFRS 9 implementation improves accounting quality by focussing on those practices. The analysis is conducted with a sample of 28 banks in Indonesia selected from the Indonesian Stock Exchange from 2012 – 2021. This study adopts a model modified from previous studies (Ahmed et al. 1999; Anandarajan et al. 2003; Anandarajan et al. 2006; Leventis et al. 2011). Using the model, this study finds that Indonesian banks perform earnings management but do not perform capital management through loan loss provisions. Although IFRS 9 implementation increases loan loss provisions, it does not affect earnings and capital management practices.